2004
DOI: 10.1113/jphysiol.2004.061663
|View full text |Cite
|
Sign up to set email alerts
|

The possum sphincter of Oddi pumps or resists flow depending on common bile duct pressure: a multilumen manometry study

Abstract: The sphincter of Oddi (SO) regulates trans-sphincteric flow (TSF) by acting primarily as a pump or as a resistor in specific species. We used the Australian possum SO, which functions similarly to the human SO, to characterize SO motility responses to different common bile duct (CBD) and duodenal pressures. Possum CBD, SO and attached duodenum (n =18) was mounted in an organ bath. External reservoirs were used to impose CBD (0-17 mmHg) and duodenal (0, 4, 7 mmHg) pressure. Spontaneous SO activity was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
(67 reference statements)
0
13
0
1
Order By: Relevance
“…It was found that the human sphincter of Oddi demonstrated unique phasic contractions, which would have an important role in regulating biliary and pancreatic duct emptying [65] . Several studies on the opossum sphincter of Oddi showed that it regulates bile like a peristaltic pump at low common bile duct pressure and as a resistor at higher common bile duct pressures [66][67][68] . Funch-Jensen et al [69] observed that the CCK injection inhibited the activity of the sphincter of Oddi of dogs, thus as bile flow increased, the gallbladder pressure remained unchanged.…”
Section: Geometry Of Biliary Duct and Flow Resistancementioning
confidence: 99%
“…It was found that the human sphincter of Oddi demonstrated unique phasic contractions, which would have an important role in regulating biliary and pancreatic duct emptying [65] . Several studies on the opossum sphincter of Oddi showed that it regulates bile like a peristaltic pump at low common bile duct pressure and as a resistor at higher common bile duct pressures [66][67][68] . Funch-Jensen et al [69] observed that the CCK injection inhibited the activity of the sphincter of Oddi of dogs, thus as bile flow increased, the gallbladder pressure remained unchanged.…”
Section: Geometry Of Biliary Duct and Flow Resistancementioning
confidence: 99%
“…A custom-built five-lumen picomanometry catheter was positioned in the biliary component of the SO via a small incision in the common bile duct [6,20]. Each catheter lumen was connected to a pressure transducer (Sorenson Transpac disposable transducer; Abbot Critical Care Systems, USA) and perfused with saline (0.02 ml/min/lumen) via a low-compliance pneumohydraulic capillary infusion system (Dentsleeve Pty.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…The manometry catheter was positioned within the SO to record proximal-SO, body-SO, and distal-SO activity ( Fig. 1B) [6]. All pressure transducers were connected to a MacLab recording system (MacLab/8S; ADInstruments, Castle Hill, Australia) and the software Chart v3.6/s (ADInstruments) was utilized.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…This organ is connected to the duodenum via extrinsic nerves, 5 and the SO function may be modified depending on common duct pressure. 17 There is significant redundancy in the regulatory mechanisms of the gastrointestinal tract. When one mechanism is severely disturbed, other mechanisms may take over the function of the primary one, to maintain the integrity.…”
mentioning
confidence: 99%